Leaving the Tub: the Nature and Dynamics of Hypercongestion in a Bathtub Model with a Restricted Downstream Exit - Yue Bao; Erik T. Verhoef; Paul Koster (Tinbergen Institute, 2020)
Hypercongestion is the situation where a certain traffic flow occurs at a combination of low speed and high density, and a more favorable combination of these could produce the same flow. The macroscopic fundamental diagram (MFD) allows for such hypercongestion, but does not explicitly describe the dynamic process leading up to hypercongestion. Earlier studies of hypercongestion on single links have, however, confirms that such dynamic processes are important to consider. The bathtub model is one class of model that can be used to investigate how hypercongestion can arise in urban areas, when drivers can choose their departure times. This paper investigates equilibrium outcomes and user costs under the realistic assumption that there is finite capacity to exit the bathtub, without which it would be hard to explain why hypercongestion would not dissolve through shockwaves originating from the bathtub exit. We find that when the exit capacity of the bathtub is lower than the equilibrium exit flow from the bathtub, no additional inefficiencies arise due to hypercongestion. However, when the exit capacity is higher than the equilibrium exit flows from the bathtub inefficiencies do occur. The implication of this result is that a restricted downstream capacity regulating hypercongestion may not be necessary because time gains in the bathtub are lost in the queue at the exit.
Keywords: R4; R41; R42; 330; Road traffic congestion; flow congestion; bottleneck model; bathtub model; hypercongestion; macroscopic fundamental diagram